MANFAAT POWERPOINT INTERAKTIF PADA PEMBELAJARAN DARING - Yunistita Yunistita; Jainal Togatorop (Universitas Quality, 2023)
The learning process during the COVID-19 pandemic was diverted using an online system, where some adjustments had to be made to keep achieving maximum learning targets. One of the interesting learning media that can be used is the use of interactive PowerPoint applications which are proven to be able to increase students' interest and motivation, as well as improve their learning achievement.Interactive Powerpoint is an interactive slide that contains learning material so that users can use it to get information and knowledge from the media. The method of this literature study is a systematic review (systematic literature review). Based on the results of literature study research, that the use of interactive powerpoint as a learning media makes it easier for students to understand the subject matter, its use is practical, conveys information clearly because the presentation is more attractive so as to foster motivation and improve student learning outcomes.